Legal Protection For Children As Victims Of Domestic Violence (Women And Children Protection Unit, Medan City Police) - Imam Saputra; Abdul Rahman Maulana Siregar; Suci Ramadani (JURNAL HUKUM SEHASEN, 2026)
This research aims to identify the factors that cause domestic violence against children and to analyze the role of the Unit for the Protection of Women and Children (PPA) of the Medan Police in providing legal protection for child victims. The study uses an empirical legal research method with a juridical approach. Data were obtained through interviews with officers from the Unit for the Protection of Women and Children (PPA) of the Medan Police and literature studies on relevant laws, books, and journals. The results show that domestic violence against children is caused by various interrelated factors, including economic hardship, low educational levels, patriarchal culture, psychological pressure, substance abuse, and disharmonious family relationships. The Unit for the Protection of Women and Children (PPA) of the Medan Police plays three main roles: preventive efforts through public legal education, repressive efforts through law enforcement against perpetrators, and rehabilitative efforts through psychological and social recovery for victims. However, the implementation of legal protection for child victims is not yet optimal due to limited human resources, insufficient facilities, and weak inter-agency coordination. Strengthening institutional cooperation and public legal awareness is essential to achieve effective and sustainable protection for children who are victims of domestic violence.